USE OF MUELLER-HINTON BROTH AND AGAR IN THE GERM TUBE TEST - Mattei, Antonella Souza; Alves, Sydney Hartz; Severo, Cecília Bittencourt; Guazzelli, Luciana da Silva; Oliveira, Flávio de Mattos; Severo, Luiz Carlos (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Candida albicans is often isolated from clinical samples, thus its presumptive differentiation from other species of the same genus can be based on its ability to form the germ tube in human serum. Nevertheless, there are two other species that share this characteristic: C. dubliniensis and C. africana. The aim of this study was to compare four different substrates to perform the germ tube (GT) test. The Candida spp. isolates were identified using a manual system (135 C. albicans, 24 C. tropicalis and one C. dubliniensis). The germ tube test was performed with fresh, previously frozen serum and Mueller-Hinton (MH) broth and agar. GT was observed in 96% (130/136) of the isolates through the fresh serum technique, 94% (128/136) through previously frozen serum, 92% (125/136) in MH agar, and 90% (122/136) in MH broth. The sensitivity of each test was higher than 90%, with 100% specificity. Both the MH agar and broth were able to identify the true positives, and false positives were not found. However, some C. albicans isolates were not identified. MH agar and broth may be used in laboratory for the rapid presumptive identification of C. albicans, as an alternative method for germ tube test.